The Possible Regulation Model To Optimize The Automatic Exchange Of Information (Aeoi) In Indonesia Through Directorate General Of Taxation, Ministry Of Finance And Financial Services Authority - Tivana Arbiani Candini; Putri Purbasari Raharningtyas Marditia; Kelly Kelly Kwannaka; Jeanny Liany (International Journal of Business, Economics, and Social Development, 2022)
Tax Treaty is a bilateral(two-party) agreement made by two or more than two countries to resolve some issues involving double taxation, transfer pricing, and treaty shopping. Several governments and organizations use model treaties generally as starting points, such as OECD Model Convention and US Model Convention. As a member of G20, Indonesia has participated in The Automatic Exchange of Information (AEoI) provides for the automatic exchange of predefined set of financial accounts information between tax authorities, based on The Common Reporting Standard (CRS), as also mentioned in Tax Information Exchange Agreement (TIEA) implemented in 2018. In order to implement AEoI the Indonesian regulator needs to review the Banking Law and the Tax Provisions and Procedures,  There is an urgent need to regulate a regulation as a standard that will be used in CSR, support the tax reform and to enhance the capacity and the authority of Directorate General of Taxation, Ministry of Finance and Financial Services Authority, while still considering the protection for the Bank Secrecy. This research will formulate a model regulation that can facilitate the implementation of the AEoI, by carrying out a study in 3 countries, which is Indonesia, Malaysia and Singapore